Brexit and European doctors' decisions to leave the United Kingdom: a qualitative analysis of free-text questionnaire comments - Adrienne Milner; Rebecca Nielsen; Emma Norris (BMC, 2021)
Abstract Background Quantitative evidence suggests that Brexit has had a severe and negative impact on European doctors, with many medical staff leaving the UK. This study provides a detailed examination of European doctors' feelings towards Brexit, their intentions to leave the UK, and factors that may contribute to their potential decisions to migrate. Methods An online questionnaire which included three optional free-text questions explored self-identifying UK-based, European doctors' views of Brexit. The three questions prompted responses on how Brexit has impacted their personal lives, their professional lives, and their future migration decisions. Fifty-nine doctors participated in the questionnaire with 52 (88.1%) providing one or more responses to the three free-text questions. Twenty-seven doctors provided answers to all three free-text questions (51.9% of included sample). Thematic analysis was used to analyse this qualitative data. Results Brexit was reported by the majority of participants to have a profound impact, although some respondents felt it was too soon to assess the potential consequences. Five themes emerged including: feeling unwelcome in the UK, Brexit as racism, uncertainty on legal ability to work, strain on relationships, and in contrast, a current lack of concern about Brexit. Conclusions To mitigate the adverse personal and professional impact of Brexit, healthcare providers should provide financial and legal support to doctors applying for settlement in the UK, ensure they are addressing issues of racial and ethnic inequality in hiring, promotion, and pay, and work towards making clinical work environments inclusive for all staff and patients.